2000
DOI: 10.1093/oxfordjournals.schbul.a033458
|View full text |Cite
|
Sign up to set email alerts
|

A Prospective Cohort Study of Genetic and Perinatal Influences in the Etiology of Schizophrenia

Abstract: In this study, we examined whether fetal hypoxia and other obstetric complications (OCs) are related to risk for adult schizophrenia; whether such effects are specific to cases with an early age at onset; and whether the obstetric influences depend on, covary with, or are independent of familial risk. Subjects were 72 patients with schizophrenia or schizoaffective disorder; 63 of their siblings not diagnosed with schizophrenia; and 7,941 nonpsychiatric controls, whose gestations and births were monitored prosp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

8
142
0
12

Year Published

2002
2002
2012
2012

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 193 publications
(162 citation statements)
references
References 88 publications
(127 reference statements)
8
142
0
12
Order By: Relevance
“…1,5,[7][8][9][10] A recent review by Schmidt-Kastner and colleagues 11 suggested that susceptibility genes for schizophrenia were more likely than randomly selected genes to be regulated by hypoxia/ischemia and/or expressed in the cerebrovasculature. In fact, a substantial fraction of the genes reported to be significantly associated with schizophrenia in at least two published studies fit this description, even though only 1-2% of known genes are involved in hypoxia-induced regulation.…”
Section: Introductionmentioning
confidence: 99%
“…1,5,[7][8][9][10] A recent review by Schmidt-Kastner and colleagues 11 suggested that susceptibility genes for schizophrenia were more likely than randomly selected genes to be regulated by hypoxia/ischemia and/or expressed in the cerebrovasculature. In fact, a substantial fraction of the genes reported to be significantly associated with schizophrenia in at least two published studies fit this description, even though only 1-2% of known genes are involved in hypoxia-induced regulation.…”
Section: Introductionmentioning
confidence: 99%
“…The heritability of performance deficits on measures of executive function, vigilance, and declarative memory has been demonstrated in twin studies (Cannon et al, 2000;Goldberg et al, 1990) and in studies of first degree relatives Faraone et al, 1995). This has lead to the suggestion that genetic liability for schizophrenia is at least partly mediated by deleterious effects on the brain regions associated with these cognitive functions, including pre-frontal and medial temporal lobe regions (Weinberger et al, 2001 Recent reviews of schizophrenia genetics (Craddock, O'Donovan, & Owen, 2005) have highlighted the potential role of a number of candidate genes in conferring liability to the disorder.…”
Section: Introductionmentioning
confidence: 99%
“…For example, DHEA and DHEAS decrease neuronal death following anoxia (Marx et al, 2000b), and obstetrical complications resulting in hypoxia are associated with increased schizophrenia risk (Dalman et al, 2001;Cannon et al, 1999Cannon et al, , 2000Geddes et al, 1999). Allopregnanolone demonstrates anticonvulsant actions in a number of seizure paradigms (Kokate et al, 1994(Kokate et al, , 1996Devaud et al, 1995;Belelli et al, 1989) and exhibits pronounced protective effects against neurodegeneration in a mouse model of Niemann-Pick type C disease .…”
Section: Introductionmentioning
confidence: 99%